CaV1.3 L-Type Calcium Channels Increase the Vulnerability of Substantia Nigra Dopaminergic Neurons in MPTP Mouse Model of Parkinson’s Disease - Verma, Aditi; Ravindranath, Vijayalakshmi (Frontiers in Aging Neuroscience, 2020)
Mechanisms underlying the selective vulnerability of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) over those in the ventral tegmental area (VTA) to degeneration in Parkinson’s disease (PD) remain poorly understood. DA neurons of SNpc and VTA are autonomous pacemakers but pacemaking in SNpc but not VTA is accompanied by calcium influx through L-type calcium channel, CaV1.3 contributing to increased intracellular calcium and hence to cell death. CaV1.342A, an alternatively spliced short variant of CaV1.3 has increased calcium influx. We, therefore studied the role of CaV1.342 (full-length channel) and CaV1.342A in mouse SNpc in PD pathogenesis by quantifying mRNA levels of CaV1.342 and CaV1.342A in SNpc and followed the change in their levels in MPTP induced parkinsonism mouse model. Using in situ hybridization and immunohistochemistry we observed the localization of mRNA of CaV1.342 and CaV1.342A in tyrosine hydroxylase (TH) positive DA neurons. Further, mRNA levels of CaV1.342A were higher in SNpc as compared to cortex. Upon MPTP treatment, mRNA levels of CaV1.342 and CaV1.342A maintained their levels in SNpc in spite of the loss of 50% of the DA neurons. This indicates that the expression of CaV1.342 and CaV1.342A is maintained at a robust level during the degenerative process in the parkinsonism model.